Mouse immunoglobulin isotypes mediating cytotoxicity of target cells by eosinophils and neutrophils. - López, A F (1983)
The cytotoxic activity of mouse eosinophils and neutrophils in the presence of antibodies of different isotypes has been studied. Mouse monoclonal anti-hapten antibodies of all the known mouse immunoglobulin isotypes have been used to coat hapten-coupled, 51Cr-labelled target cells. Two different target cells have been used, sheep red cells, as a model for intracellular killing, and BW cell line cells, as a model for extracellular killing. It is shown that both eosinophils and neutrophils lyse sheep red cells coated with IgG1, IgG2a and IgG2b and to a lesser extent IgG3. No killing is detected when sheep red cells are coated with IgM, IgA or IgD. Neutrophils, but not eosinophils are shown to lyse IgE-coated sheep red cells. When tested against BW cells, neutrophils have been found to induce high levels of 51Cr release in the presence of IgG1, IgG2a, IgG2b and IgE, but not when IgG3, IgM, IgA or IgD were used. In contrast, no killing of BW cells by eosinophils could be detected with any of the different antibody isotypes tested. However, it is shown that eosinophils are able to kill IgG-coated BW cells when hapten coupling is increased to maximum levels or when complement is added into the system, emphasizing our previous results showing that eosinophils require much higher levels of ligands than neutrophils to be effective. To test the possibility that eosinophils have a weak IgE receptor, complement was added to IgE-coated BW cells by means of a monoclonal IgM anti-Thy-1 antibody but no cytotoxicity was detected. It cannot be completely excluded that eosinophils have IgE blocking a putative IgE receptor.